TO THE ISSUE OF AN EFFECTIVE MODEL OF PRIVATE PENSION PROVIDING IN THE POST-WAR DEVELOPMENT PARADIGM OF UKRAINE - STETSENKO, Bogdan; BIRIUK, Serhii; STRIZHAK, Artur; LYTVYNIUK, Artem (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article examines the development of the private pension system in Ukraine during the post-war period. It is emphasized that before the onset of open aggression against our state, the pension system was characterized by significant imbalances. The Pension Fund of Ukraine constantly experienced a resource deficit, the size of pensions was one of the lowest in Europe, and the private pension system effectively did not perform its functions. On one hand, the operation of the solidarity state pension insurance system caused negative public resonance. On the other, a distrust of the activities of private pension funds was formed among ordinary citizens, hence the quantitative parameters of their activity were minimal. Evidently, during the period of martial law, key efforts were directed toward the development of the national security and defense sector. Currently, the maximum amount of financial resources, including those from external partners, are directed towards state defense. However, even under such conditions, ignoring problems in the pension system causes additional tension in society and can be used as a pretext for internal destabilization. Accordingly, the state must now direct efforts to form a strategic scenario for the modernization of the pension system. Clearly, in the post-war period, the development of the private pension system and the pension system as a whole will be one of the key issues. It is reasoned that the key trends in the development of private pension provision in Ukraine in the post-war period will be determined by various factors: migration processes, the volume of resources in households, the state of the domestic stock market, and the effectiveness of reforms in this area. The development of private pension providing will become a powerful impetus for the activation of investment processes, forming a financial basis for attracting long-term resources into the national economy. But all of these tasks require a comprehensive approach from the state, in which public interests will be key, and not the main interests of the leading financial and industrial groups.